2017
DOI: 10.19044/ejes.v4no2a1
|View full text |Cite
|
Sign up to set email alerts
|

The Possibilities of Assessing Students’ Scientific Inquiry Skills Abilities Using an Online Instrument: A Small-Scale Study in the Omusati Region, Namibia

Abstract: The objectives of this study were to; explore the possibilities and feasibilities of an online assessment of students' scientific inquiry skills; examine the psychometric properties of the test; ascertain the ability level of the 9 th and 11 th graders scientific inquiry skills. The sample consisted of the ninth and eleventh graders (N=118, 44 boys and 74 girls; age mean=16.42, and (SD) =1.25). In the test of scientific inquiry skills, students were required to use their cognitive skills to answer questions ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…We could not agree more with the literature about that when we noticed the same in our study. One might generalise these results even with some controversial results noticed in other studies, as it was with Kambeyo (2017) when he found no relationship between patents' level of education and pupils' achievement. At the same time, the researcher suggested that economic reasons might cause such a result.…”
Section: Discussionsupporting
confidence: 55%
“…We could not agree more with the literature about that when we noticed the same in our study. One might generalise these results even with some controversial results noticed in other studies, as it was with Kambeyo (2017) when he found no relationship between patents' level of education and pupils' achievement. At the same time, the researcher suggested that economic reasons might cause such a result.…”
Section: Discussionsupporting
confidence: 55%
“…Following Klahr and Dunbar's [29] "Dual Space Search," SR models usually cover the domain "conducting scientific investigations" [24] and exhibit at least a three-fold structure involving the facets "hypothesis," "experiment," and "conclusion". However, the respective models differ in the degree of sub-division into up to 9 facets (see Figure 1) [10,24,26,[28][29][30][31][32][33][34][35][36][37]. For example, the model developed by Fischer and colleagues [30] also covers the problem identification, that is, the analysis of the underlying phenomenon before the generation of hypotheses.…”
Section: Models For Scientific Reasoning Competencymentioning
confidence: 99%
“…Moreover, "testing hypotheses" is subdivided into a construction phase (cf. the different notions of planning in Figure 1) and "evidence generation," which is comparable to experimentation and observation [26,28,31]. The last facet of Klahr and Dunbar's [29] model can be divided into "evidence evaluation," such as the preparation and interpretation of experimental findings [26,32], and "drawing conclusions".…”
Section: Models For Scientific Reasoning Competencymentioning
confidence: 99%
“…Questionnaire for inquiry abilities is given before and after the learning process which consists of 20 statements with 5 alternative answers (Likert scale). The observation sheets and inquiry ability questionnaires were developed from the synthesis of inquiry stages which led to the emergence of the inquiry abilities of students according to Lou, Blanchard, and Kennedy (2018); Zulfiani and Herlanti (2018); Kambeyo (2017); Wenning (2007); Lukac (2015); Wu and Hsieh (2006); Mumba, Chabalengula and Wise (2007);and the National Research Council (1996). The inquiry syntax used to find out the student inquiry abilities can be seen in Table 2.…”
Section: Data Collectionmentioning
confidence: 99%
“…In addition, computers in science learning are appropriate and comfortable, especially when content is used well (Tuysuz, 2010).The use of inquiry-based virtual chemistry laboratories that have been carried out in this study can improve students' inquiry skills before and after the learning process. According to this diagnosis of students' abilities, certain learning environments can create student inquiry skills (Kambeyo, 2017). Inquiry learning, using media plays a role in improving students' thinking skills.…”
Section: Tablementioning
confidence: 99%